Emotional intelligence and projects - Clarke, Nicholas 1966-; Howell, Ranse (2009)
Of the report -- Emotions, emotional intelligence, and projects -- Study one: The relationships between emotional intelligence abilities, project manager competences, and transformational leadership behaviors -- An evaluation of the impact of emotional intelligence training -- Implications of findings, directions for future research, and overall conclusions -- Developing emotional intelligence training : theoretical and empirical underpinnings -- Appendices. Appendix 1: Semi-structured interview schedule -- Appendix 2: Exercise 1 : emotional self-awareness -- Appendix 3: Exercise 2 : perceiving emotions -- Appendix 4: Exercises 3 and 4 : verbally demonstrating empathy and practicing demonstrating empathy -- Appendix 5: Exercise 5 : role plays to show practice in rapport, empathy, and anticipating and responding to emotions -- Appendix 6: Exercise 6 : the organization's emotional climate.
Title from title screen. - Includes bibliographical references
Keywords: Emotional intelligence; Executives -- Training of; Group relations training; Project management -- Psychological aspects; Project management -- Research; Emotional Intelligence; Gestion de projet; Recherche; Intelligence émotionnelle; Relations humaines; Formation; Gestion de projet; Aspect psychologique; Project management; Research; Executives; Training of; Project Management (PM); Research